2014
DOI: 10.1016/j.yjmcc.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial quality control in the myocardium: Cooperation between protein degradation and mitophagy

Abstract: Mitochondria are critical for cardiomyocyte survival and maintenance of normal cardiac function. However, changes in the extra- or intracellular environments during stress can cause excessive damage to mitochondria and lead to activation of cell death. In fact, there is evidence that mitochondrial dysfunction is an important contributor to both development of heart failure and the aging process. To counteract the adverse effects resulting from mitochondrial damage, cells have evolved mitochondrial quality cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 101 publications
(128 reference statements)
1
75
1
2
Order By: Relevance
“…Mitochondria are important for cardiomyocyte survival and maintenance of normal cardiac function [20]. Emerging evidence suggest that mitochondrial dysfunction may lead to the genesis of heart failure, which indicates a close association between mitochondrial biogenesis and cardiac function [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are important for cardiomyocyte survival and maintenance of normal cardiac function [20]. Emerging evidence suggest that mitochondrial dysfunction may lead to the genesis of heart failure, which indicates a close association between mitochondrial biogenesis and cardiac function [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Soubannier et al observed that subunits of Complexes II, III, and IV are differentially incorporated into the vesicles, whereas proteins of complex I and ATP synthase are excluded ( Soubannier et al, 2012b). The reasoning behind this additional selectivity is still not understood, although size differences and stress-specific protein removal have been suggested (Hammerling and Gustafsson, 2014). The discovery that MDV formation requires the presence PINK1 and Parkin has been another important recent development (McLelland et al, 2014).…”
Section: Removal Of Oxidised Proteins From the Mitochondriamentioning
confidence: 99%
“…Although MAD is stimulated by oxidative stress, damaged proteins accumulate in the TauTKO heart, suggesting that the MAD pathway must play a minor role in the removal of damaged proteins in the TauTKO heart. Also, the mitochondrial matrix, which is subject to extensive quality control, contains AAA proteases that remove proteins damaged by ROS (Hammerling and Gustafsson 2014). Particularly noteworthy in the present study is the observation that mitoTEMPO treatment normalizes ubiquitinated protein content, suggesting that ROS inhibits protein degradation, a property of the UPS, but not that of the MAD pathway (Taylor and Rutter 2011;Voigt et al 2013;Reyskens and Essop 2014;Segref et al 2014).…”
Section: Discussionmentioning
confidence: 53%
“…A common cause of excessive accumulation of ubiquitinated proteins in the diseased heart is impaired proteasome function. Because the β5 subunit of the 26S proteasome functions as the primary protease involved in the degradation of oxidized proteins (Ferrington et al 2005;Hammerling and Gustafsson 2014), the effect of taurine deficiency on β5 subunit activity was evaluated. As seen in Fig.…”
Section: Taurine Depletion Decreases Ubiquitin-proteasome Systemmentioning
confidence: 99%